Design and fabrication of infrared auto on/off pet water fountain / Ainin Sofea Abd Razak - Abd Razak, Ainin Sofea (2023)
Generally, pet owners will use bowls to feed and give water to the pets for their daily needs. However, some of the cat owners are busy with work life which eventually do not have the time to feed the pets, especially in supplying drinking water. This is very dangerous as the water will get contaminated and affect the pet’s health. Due to these reasons, this project will propose to design and fabricate a pet water fountain with an Infrared Sensor which has an Auto On-Off switch that will limit water output automatically. It is very important to limit and provide clean water for pets to prevent the pets from getting various types of diseases. When the pet comes within a certain distance of this auto water fountain, a fountain of water will erupt, and it will turn off and on again when there is no movement. I hope that this design can be helpful to solve the problems for the pet owner’s problems in giving their pets drinking water.